Pengaruh Etika, Pendidikan, dan Pengalaman terhadap Kualitas Audit dengan Profesionalisme sebagai Variabel Intervening - Nurul Alfiyah; Siti Maria Wardayati; Agung Budi Sulistiyo (Jurnal Ekonomi Akuntansi dan Manajemen, 2018)
This study aims to examine and analyze the influence of ethics, education and experience to professionalism and to test and analyze the effect of ethics education, experience and professionalism of the quality audit at the office of the Inspectorate of Banyuwangi. Where the sampling technique using census method with auditors who have the certification criteria of functional positions auditor (JFA) and follow continuous professional education and training (continuing professional education) totaling 28 people. The results showed that ethics significant effect on audit quality. Then the second hypothesis education variable has no effect on audit quality, this indicates the second hypothesis is rejected. The third hypothesis is that experience does not significantly affect professionalism. Fourth hypothesis ethics significantly affect audit quality. Education not significant effect on audit quality, this indicates a fifth hypothesis is rejected. The sixth hypothesis experience significant effect on audit quality. And the results of the seventh hypothesis professionalism significant effect on audit quality. Keywords: ethics, education, experience, professionalism and quality of the audit.